Test podstawowych celów transakcji a międzynarodowe unikanie opodatkowania – uwagi na tle Projektu BEPS - Lipniewicz, Rafał (Kwartalnik Prawa Podatkowego, 2016)
In 2015 the Organisation for Economic Co-operation and Development (OECD) published revisions to tax principles, which are based on a 15-point action plan on Base Erosion and Profit Shifting (BEPS). BEPS Action 6 recommends a new Principal Purposes Test clause to prevent treaty abuse. The purpose of this article is to analyze legal and economic aspects of the “principal purpose” standard, particularly in the context of the principle of legal certainty.